Penggunaan Gadget dalam Meningkatkan Prestasi Belajar Bahasa Arab Masa Pandemi Covid 19 Siswa Kelas VI MI Arriyadh Hidayatullah Bontang Tahun Pembelajaran 2020/2021 - Muchlis, Hijrah; Jamaluddin, Jamaluddin (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This article addresses the use of gadgets in improving Arabic language learning achievements during the COVID-19 pandemic for sixth-grade students at MI Ar-Riyadh Hidayatullah Bontang by Arabic language subject teachers, aiming to implement distance learning systems that enable students to excel in their studies. The research background focuses on the use of gadgets in education during the recent year of the COVID-19 pandemic. The researcher's objectives are to understand the impact of gadget use on learning achievements and to identify the actions taken by teachers to enhance Arabic language learning achievements at MI Ar-Riyadh Hidayatullah Bontang, specifically in the sixth grade. The research method employed is qualitative, using data collection methods such as observation, interviews, and documentation, followed by data analysis involving data reduction, data presentation, and conclusions. The research findings indicate that gadgets have had a significant impact on the students' learning, and while the impact has been mostly positive, it has also been gratifying in improving student achievements. The use of gadgets in improving Arabic language learning achievements for sixth-grade students at MI Ar-Riyadh Hidayatullah Bontang has resulted in both positive and negative impacts. The positive impact can turn negative when overused, and student achievements are evaluated based on intellectual performance, attitude, skills, as well as obedience and discipline. In conclusion, the current impact of gadget use is of concern as it tends to lean more towards negative aspects due to the evolving challenges of the modern era. MI Ar-Riyadh needs to remain focused on maintaining the existing learning achievements through various methods and approaches to withstand the waves of declining academic performance and to nurture a generation of excellence that is well-prepared to face challenges.